PO.2.44 Catastrophic anti-phospholipid syndrome and peripartum: a new observation!. (27th September 2022) - Bouziani, N; Kella, A; Belabbas, A; Bouadjadj, K; Hakem, D
Abstract : Catastrophic anti-phospholipid syndrome (CAPS) is a rare (1%) severe, and accelerated form of antiphospholipids syndrome (APS) characterized by the almost simultaneous occurrence of microcirculatory thrombosis in multiple locations leading to multi-organ failure involving compromissing vital prognosis (40% of deaths). Among the risky situations pregnancy has been reported by many authors who include the HELLP syndrome. Observation: 34 years old woman, P5P5A0 with a history of deep vein thrombosis of the lower limbs 9 months earliers present during a pregnancy at 25th week of amenorrhea successive hepatic, coronary, cerebral thrombotic events and pulmonary embolism. A HELLP syndrome imposes the extraction of a fetus at the 30th week of pregnacy. The diagnosis of APS was made on the history of DVT and the clinical context (coronary, neurological damage) and will be confirmed by the presence of anti-cardiolipin antibodies (ac CL) type IgG at 30UI. Speckled-type antinuclear antibodies and anti-SSA antibodies were positive at 1/320, beta2 glycoprotein antibodies and IGM-type anti-cardiolipin antibodies were positive at 36UI.The abdomino-pelvic ultrasound visualized a liver increased in size to 20mm with heterogeneous regular contours and a spleen increased in size to 164mm in regular contour with the Doppler finding a portal trunk and dilated but permeable superhepatic veins. Cardiac echo-doppler found an EF at 40%, a dilated left ventricle and kinetic disorders. Coronary angiography found healthy coronaries. In front of the table associating a successive attack of 3 organs (liver, heart, brain) in one week of interval associated with the presence of anti-phospholipid antibodies allowed to make the diagnosis of SCAPL. The patiente was then put on Lovenox at a curative dose and double anti-platelet aggregation (Aspégic 100 mg and Plavix 75 mg/d) associated with an enzyme-converting enzyme inhibitor and a cardio-selective beta-blocker. Similarly, a bolus of corticosteroid 1 g/d was initiated for 3 days with an oral relay of prednisone equivalent at 1 mg/d with progressive degression. The relay of heparin by Sintrom and the addition of plaquenil at 200 mg/d consolidated the treatment. Tubal ligation was discussed. The evolution was favorable on the biological and morphological clinical level. Cardiac reassessment and abdominal CT angiography were scheduled. During APS, the obstetrical pathology is often in the foreground and frequently allows the diagnosis to be evoked. Patients with APS remain at high risk of developing obstetric complications involving the maternal and fetal prognosis. The successive thrombotic occurrence in the peripartum announces a SCAPL, darkens the prognosis and requires intensive multidisciplinary emergency management. Nevertheless, the prognosis of APS has improved in recent years, allowing patients to access maternity in the best possible safety conditions.